2019
DOI: 10.1016/j.celrep.2019.10.025
|View full text |Cite
|
Sign up to set email alerts
|

DUX4-Induced Histone Variants H3.X and H3.Y Mark DUX4 Target Genes for Expression

Abstract: SUMMARY The DUX4 transcription factor is briefly expressed in the early cleavage-stage embryo, where it induces an early wave of zygotic gene transcription, whereas its mis-expression in skeletal muscle causes the muscular dystrophy facioscapulohumeral dystrophy (FSHD). Here, we show that DUX4 induces the expression of the histone variants H3.X and H3.Y. We have used a myoblast cell line with doxycycline-inducible DUX4 to show that these histone variants are incorporated throughout the body of DUX4-induced gen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
45
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(56 citation statements)
references
References 40 publications
3
45
1
Order By: Relevance
“…Small populations of DUX4-positive myotubes are thought to drive pathogenesis in FSHD [2][3][4]. We found 0.1% (16/15,687) of nuclei expressed DUX4 using single-nucleus RNA-seq which is lower than the reported 0.5% (1/200 in myotube nuclei) [8,10,16,27] possibly due to variability in expression levels of DUX4 between individuals. However, the percentage of DUX4-affected nuclei we found (3.7%, 583/15,687) is higher than that reported in FSHD single myocytes (0.55%, 27/4902) [29].…”
Section: Discussioncontrasting
confidence: 69%
See 3 more Smart Citations
“…Small populations of DUX4-positive myotubes are thought to drive pathogenesis in FSHD [2][3][4]. We found 0.1% (16/15,687) of nuclei expressed DUX4 using single-nucleus RNA-seq which is lower than the reported 0.5% (1/200 in myotube nuclei) [8,10,16,27] possibly due to variability in expression levels of DUX4 between individuals. However, the percentage of DUX4-affected nuclei we found (3.7%, 583/15,687) is higher than that reported in FSHD single myocytes (0.55%, 27/4902) [29].…”
Section: Discussioncontrasting
confidence: 69%
“…Altered myogenesis in FSHD cells has been shown in previous studies [26]. Recently, a study showed upregulation and incorporation of alternate histones H3.X and H3.Y following DUX4 expression [27]. In this study, H3.Y (AKA RP11-432M8.17) has increased expression in FSHD2 cells and is included in our FSHD-induced genes.…”
supporting
confidence: 69%
See 2 more Smart Citations
“…A recent study by Resnick et al (2019) further showed that DUX4 induces H3.X and H3.Y expression, as well as causes the increased incorporation of these histone variants into the nucleosomes of its target genes [102]. H3.X and H3.Y are associated with relaxed chromatin regions and have been found to greatly facilitate DUX4 target gene-specific induction and perdurance.…”
Section: Gene Regulationmentioning
confidence: 98%